(untitled) (Journal of the College of Basic Education, 2023)
The British presence in the Arabian Gulf was exposed to competition from other European powers.And since an early stop, led by the Portuguese, the Dutch and the French, Britain was ableThrough a long political and military struggle that lasted nearly three centuries, it got rid of its competition.European powers, but that does not mean an end to the troubles that faced Britain, as soonThe Russian penetration appeared clearly and posed a threat to British interests in the ninth century.Tenth, following the entry of Russian ships into the waters of the Arabian Gulf and their frequenting of ports and citiesthe eastern and western coasts.And since the academic studies did not deal with Britain’s position on the Russian activity inThe Arabian Gulf during the nineteenth century in independent research. The researcher decided to delve intoThis subject, despite his awareness of the difficulty and scarcity of sources covering this period of time.Russian influence in the region. However, Russian activity in all its forms has been highlighted.political, commercial and medical, based on the information provided and the study trusted it throughAccessible sources, such as Russian documents, which were dealt with by a number of specialized professors.In addition to other sources, which were published in the Bahraini Document Magazine, and these revealed theMysterious aspects regarding Russian activity in the Arabian Gulf in the period under study.The use of other studies and reference to Arab and foreign sources was of assistance to the researcher inFollow-up of the origins of this activity and its development until the end of the nineteenth century.